The Merck manual of diagnosis and therapy. - Beers, Mark H.; Berkow, Robert, 1929-; Merck Research Laboratories (Whitehouse Station, N.J. : Merck Research Laboratories, 1999)
A compendium of facts and information on hundreds of diseases, including etiology, symptoms and signs, diagnosis and treatment.
1. Nutritional disorders -- 2. Endocrine and metabolic disorders -- 3. Gastrointestinal disorders -- 4. Hepatic and biliary disorders -- 5. Musculoskeletal and connective tissue disorders -- 6. Pulmonary disorders -- 7. Ear. nose, and throat disorders -- 8. Ophthalmologic disorders -- 9. Dental and oral disorders -- 10. Dermatologic disorders -- 11. Hematology and oncology -- 12. Immunology; Allergic disorders -- 13. Infectious diseases -- 14. Neurologic disorders -- 15. Psychiatric disorders -- 16. Cardiovascular disorders -- 17. Genitourinary disorders -- 18. Gynecology and obstetrics -- 19. Pediatrics -- 20. Disorders due to physical agents -- 21. Special subjects -- 22. Clinical pharmacology -- 23. Poisoning -- 24. Index.
"Centennial edition"--Cover.
The 16th edition was published in 1992.
Accompanied by a facsimile of the 1899 edition: Merck's manual of the materia medica.
Includes index.
Keywords: Medicine -- Handbooks, manuals, etc; Diagnosis -- Handbooks, manuals, etc; Therapeutics -- Handbooks, manuals, etc; Diagnosis; Drug Therapy